Analysis of the relationship between the stage of economic development and the state of cluster development - Paraušić, Vesna; Domazet, Ivana; Simeunović, Ivana (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Starting from the fact that clusters contribute to the competitiveness of industry sectors and the high standard of living in regions where clusters operate, the aim of this paper is to show the relationship between the stage of economic development and the state of cluster development at the level of national economies. Using the ANOVA statistical method the authors have accepted the hypothesis that the state of cluster development in national economies varies depending on the stage of economic development. In order to evaluate the state of cluster development in the country and the stage of economic development, the authors used the secondary data from the World Economic Forum (WEF), published in “The Global Competitiveness Report 2013–2014”. Although the stage of economic development is influenced by many economic and political factors, the authors assume that the stage of economic development predominantly depends on the decision and willingness of political and business leaders to lead the country to higher stages of economic development and sustainable economic growth. Their decision has an impact on cluster development in the country, and therefore influences the possibility of clusters to improve economic development and national competitiveness, especially in emerging markets and developing economies
Argumenta Oeconomica, 2017, Nr 2 (39), s. 279-306
Keywords: clusters; competitiveness; economic development